If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6z=-49-z
We move all terms to the left:
6z-(-49-z)=0
We add all the numbers together, and all the variables
6z-(-1z-49)=0
We get rid of parentheses
6z+1z+49=0
We add all the numbers together, and all the variables
7z+49=0
We move all terms containing z to the left, all other terms to the right
7z=-49
z=-49/7
z=-7
| -8-6u=4u+8-8u | | 0.49=0.13x | | -16.6x+19.2=11 | | X20-92=-20x | | -6z-3=-9-5z | | 7x=–70 | | 6.95+0.29c=17.10 | | 12x-5-7x-2=0 | | −16.6x+19.2=11 | | k−7+2=-5 | | 7(8+4z)-15z=0 | | –2s=9+7s | | X2-92=-20x | | x+57-x+77=120 | | 0.5(10-8x)=11-(5x+13) | | 30x-40x=110 | | 4x-6x=70 | | 4(1.08)^x+3=18 | | x+74-49+x=79 | | v6-3.6=-22.8 | | (x)=4x^2-44x+121 | | 2+7y=-y+8+7y | | (12–4x)=3–x | | .(12–4x)=3–x | | 3(x-8)-6=-3 | | -5a+3=18 | | 31(6x-20)=180 | | X+10-4x+2=-25 | | 9x-4=5+9x | | 5p+3=-9+7p | | (-13+x-5-4x=-9) | | 0.46x=1 |